MAKING EXTENSIVE READING EVEN MORE STUDENT CENTERED - Jacobs, George; Renandya, Willy (Indonesian Journal of Applied Linguistics, 2015)
Abstract: This article begins by explaining the student centered learning paradigm.Â  Next, the article explains various features of a student centered approach to education and how extensive reading (ER), as it is most often practiced, fits with those features. Â The bulk of the article suggests how ER might be implemented to make it even more learner centered.Â